STUDY ON MATERNAL TESTOSTERONE HORMONE IN FEMALE BROODSTOCKS AND EGG OF CATFISH (Clarias gariepinus) - Rahmadiah, Triayu; Junior, Muhammad Zairin; Alimuddin, Alimuddin; Diatin, Iis (Jurusan Perikanan dan Kelautan, 2024)
This study aimed to track maternal testosterone hormone in catfish (Clarias gariepinus) eggs as an endogenous factor causing cannibalism. The fish used were female catfish broodstocks that had never been spawned before, with an average weight of 450.0±62.00 g and a total length of 35.4±3.53 cm. The male broodstock had an average weight of 810.0±85.00 g and a total length of 46.1±5.83 cm. The broodstock were maintained separately by sex in 3×1×1 m3 hapa nets, with a stocking density of two females and one male (2:1 ratio). The study employed a completely randomized design (CRD) with treatments consisting of females injected with propylene glycol (0 µg/L body weight) (A), females injected with the hormone 17α-MT (1 µg/L body weight) (B), and females injected with the hormone 17α-MT (2 µg/L body weight) (C), each treatment replicated three times. For the observation of hormone derivatives, egg samples were collected during the pre-spawning (day 90) and post-spawning (day 91) periods. The results indicated that the testosterone levels in the catfish eggs were higher during the pre-spawning period (A: 0.6±0.03 ng/mL; B: 0.7±0.07 ng/mL; C: 1.2±0.01 ng/mL) compared to the post-spawning period (A: 0.3±0.03 ng/mL; B: 0.1±0.00 ng/mL; C: not detected). This finding suggests that, even without the injection of the 17α-MT hormone, testosterone is present in catfish eggs, albeit in small amounts.Keywords: Aggressiveness, cannibalism, inherited hormones.